Economic costs, health-related quality of life outcomes and cost-utility of a physical and psychological group intervention targeted at older adults with neurogenic claudication - Maredza, M; Kamran, K; Marian, IR; Dutton, SJ; Williamson, E; Lamb, SE; Stavros, P (BioMed Central, 2023)
Background Emerging evidence suggests that structured and progressive exercise underpinned by a cognitive behavioural approach can improve functional outcomes in patients with neurogenic claudication (NC). However, evidence surrounding its economic benefits is lacking.